2008
DOI: 10.1016/s1875-9572(08)60014-5
|View full text |Cite
|
Sign up to set email alerts
|

First Attack of Acute Urticaria in Pediatric Emergency Department

Abstract: Detailed etiologies of first-attack urticaria in children in central Taiwan were analyzed. Most importantly, we found that there was a decrease in the prevalence of various infections as causative factors as the age of the children increased. The etiologies of foods and medications were more prevalent in adolescents than in younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 11 publications
6
40
2
3
Order By: Relevance
“…The most common etiologic factors in children with acute urticaria include acute infections, food, insect bites, and parasitic infections, respectively (11,14,(17)(18)(19). In our study, the triggering factors we found were similar to those in many studies in the literature.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The most common etiologic factors in children with acute urticaria include acute infections, food, insect bites, and parasitic infections, respectively (11,14,(17)(18)(19). In our study, the triggering factors we found were similar to those in many studies in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, no significant difference was found in terms of sex in children with acute and chronic urticaria by Chang et al (10), in children with acute urticaria who presented to emergency department by Liu et al (11), or in children with food-induced urticaria by Wananukul et al (12). However, urticaria is observed more frequently in adult women compared with adult men (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations